Developmental Patterns of Religiosity in Relation to Criminal Trajectories among Serious Offenders moving from Adolescence to Young Adult - Guo, Siying (Crime & delinquency, 2021)
Using Group-Based Trajectory Models and Growth Curve Models, this study aimed to identify distinctive trajectories of religious attendance, religious importance and spirituality and how these trajectories related to changes in crime. The findings varied by measures of religiosity and types of crime. Generally, different measures of religiosity had little to do with initial offenses. A few trajectories of religious attendance and importance associated with both violent and income offenses, while changes in spirituality only related to violent offenses. Losses in religiosity may associate with elevated risks of recidivism. A small range of gains and losses in religiosity may increase the risk of recidivism, while maintaining high religiosity over time may result in a smaller growth change in recidivism.